Dampak Mie Instan terhadap Kadar Hemoglobin Mencit (Mus musculus) - Indah Anggeriani; Erni Yohani Mahtuti; Previta Zeisar Rahmawati (FORIKES, 2022)
Hemoglobin functions to carry oxygen, carbon dioxide which is circulated to body tissues. When the blood lacks hemoglobin, the body will experience anemia. One of the factors that affect hemoglobin levels is nutrition. Instant noodles are foods that are high in carbohydrates, fat, but low in protein, vitamins and minerals. The purpose of this research was to determine the effect of instant noodle concentration on hemoglobin values in mice (Mus musculus). This experimental research used a pretest-posttest design. The sample consisted of 24 female mice (Mus musculus) aged 3-8 weeks, with a body weight of 20-35 grams, which were given 4 treatments. P1 was given instant noodles 0.31 g/kgBW/day, P2 was given instant noodles 0.34 g/kgBW/day, P3 was given instant noodles 0.39 g/kgBW/day, and P4 was given instant noodles 0.50 g/kgBW /day. All were administered orally using a gastric tube. The intervention was carried out for 3 days of observation. Hb value is determined by Hb-meter. The result of the normality test is p = 0.390, the result of the homogeneity test is p = 0.839), so that a paired sample t-test can be carried out which produces a p value of less than 0.05. It can be said that there are differences in hemoglobin levels between before and after the intervention in all groups. It was concluded that instant noodles had an effect on reducing Hb levels in mice. It is recommended that if you consume instant noodles, you should add nutrients that meet the body's needs.Keywords: hemoglobin; instant noodles; oral administration ABSTRAK Hemoglobin berfungsi untuk membawa oksigen, karbondioksida yang diedarkan ke jaringan tubuh. Ketika darah kekurangan hemoglobin, maka tubuh akan mengalami anemia. Salah satu faktor yang mempengaruhi kadar hemoglobin adalah nutrisi. Mie instan merupakan makanan yang tinggi karbohidrat, lemak, tetapi rendah protein, vitamin dan mineral. Tujuan riset ini adalah untuk mengetahui efek konsentrasi mie instan terhadap nilai hemoglobin pada mencit (Mus musculus). Penelitian eksperimental ini menggunakan pretest-posttest design. Sampel berupa 24 ekor mencit (Mus musculus) betina berusia 3-8 minggu, denga berat badan 20-35 gram, yang diberi 4 perlakuan. P1 diberi mie instan 0,31 g/kgBB/hari, P2 diberi mie instan 0,34 g/kgBB/hari, P3 diberi mie instan 0,39 g/kgBB/hari, dan P4 diberi mie instan 0,50 g/kgBB/hari. Semua diberikan secara oral menggunakan sonde lambung. Intervensi dilakukan selama 3 hari pengamatan. Nilai Hb dintentukan dengan Hb-meter. Hasil uji normalitas adalah p = 0,390, hasil uji homogenitas adalah p = 0,839), sehingga bisa dilakukan paired sample t-test yang menghasilkan nilai p kurang dari 0,05. Bisa dikatakan bahwa terdapat perbedaan kadar hemoglobin antara sebelum dan sesudah intervensi pada semua kelompok. Disimpulkan bahwa mie instan berpengaruh menurunkan kadar Hb mencit. Disarankan bahwa jika mengkonsumsi mie instan, hendaknya ditambahkan zat gizi yang memenuhi kebutuhan tubuh.Kata kunci: hemoglobin; mie instan; pemberian oral